Two new species of Pogonophora from the north-east Atlantic - Southward, Eve C. (Journal of the Marine Biological Association of the United Kingdom, 1959)
Summary: Two new species of Pogonophora are described. Oligobrachia ivanovi is recorded from a depth of 730-780 fm off the mouth of the English Channel; Polybrachia capillaris is recorded from depths of 340-970 fm. at various stations off the mouth of the English Channel and one station off the north coast of Spain. Begins: "In May 1958 it was thought that all species of Pogonophora so far discovered in the north-east Atlantic belonged to the genus Siboglinum Caullery (Southward & Southward, 1958). Since then I have had the opportunity of examining further collections from deep water off the British Isles and Spain. At least two species of multitentaculate pogonophores have been discovered, and re-examination of some material collected in May 1958 shows that one of the species was also present in these collections. Although considerable material belonging to other species remains to be worked up it has been thought worth while to describe these two species first. One is widespread and can be locally abundant, while the other is the largest pogonophore so far found in the Atlantic. Both are the first Atlantic representatives of their respective genera.
Annelidabase